The Utilization of demographic knowledge in policy formulation and planning - Andorka, Rudolf, (ed.) (Leige, Belgium : International Union for the Scientific Study of Population, 1991)
Health and Population
Includes bibliographical references
1994-10-09
Keywords: Demography; Population policy; Policy planning